1987
DOI: 10.1111/j.1439-0442.1987.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Aditoprim, a New Long‐acting Dihydrofolate Reductase Inhibitor, in Heifers

Abstract: The pharmacokinetics of aditoprim, a new dihydrofolate reductase (DHFR) inhibitor, and trimethoprim (TMP) were studied in heifers following a single intravenous injection of a 10rng/kg b. w. dose. Aditoprim had a larger volume of distribution at steady state (6.5 k 0.6 Pkg) than TMP (1.1 +_ 0.1 I/kg) and this probably reflects a better tissue penetration than TMP. Both antimicrobials had the same high plasma clearance (5.0 k 1 .O Urnin). Accordingly, aditoprim exhibited a longer halflife (4-6.711) than TMP whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In contrast to the excretion of TMP in rats, more than 95% of the oral dose was recovered within 3 d. ADP showed a relatively slow elimination trend (approximately 84% of the oral dose during 0–3 d) in comparison with the rat excreta, implying that ADP would have a longer elimination half-life than TMP in the organism. This finding was further supported by the pharmacokinetic characteristics of ADP in animals 5 6 8 . ADP related radioactivity in broilers was excreted more rapidly than in other species, with a high recovery of 85.8% (about 70% in other species, Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast to the excretion of TMP in rats, more than 95% of the oral dose was recovered within 3 d. ADP showed a relatively slow elimination trend (approximately 84% of the oral dose during 0–3 d) in comparison with the rat excreta, implying that ADP would have a longer elimination half-life than TMP in the organism. This finding was further supported by the pharmacokinetic characteristics of ADP in animals 5 6 8 . ADP related radioactivity in broilers was excreted more rapidly than in other species, with a high recovery of 85.8% (about 70% in other species, Fig.…”
Section: Discussionsupporting
confidence: 53%
“…It is reported that this compound is particularly active against Enterobacteriaceae , Haemophilus , Staphylococcus , Streptococcus , Vibrio , and Aeromonas 2 . Moreover, ADP provides significant pharmacokinetic advantages, including long half-lives (6.1–11.9 h) and high tissue distribution volume (4.4–12.2 L/kg) in various animal species such as sheep 3 4 5 , cattle 6 7 8 9 , pig 10 , horse 11 , turkey 12 , dog 13 , and monkey 14 . These earlier studies have shown that ADP had a good efficacy when administered alone or combined with sulfonamides in a one-day dose for the treatment of respiratory and gastro-intestinal infections.…”
mentioning
confidence: 99%
“…The These drugs are widely used in veterinary medicine (Vree & Hekster, 1985). The apparent volume of distribution, about 5 Vkg, indicated that aditoprim is widely distributed in the body, as has already been observed in pigs (26 Vkg;Ludwig et al, 1985) and cattle (25 I/kg ;Jordan et al, 1986). This value was more than five-and ten-times higher than for TMP and sulphonamides, respectively, and reflects the good tissue penetration of the new antimicrobial.…”
mentioning
confidence: 66%
“…The elimination half-life of ADP in pigs is & 8 h, whereas the half-life of TMP is 2.5±3 h (Nielsen & Rasmussen, 1975;Ludwig et al, 1985;Jordan et al, 1987). This may be due to the fact that ADP is not metabolized to polar compounds with high renal clearance rates, like the glucuronidated O-demethyl derivatives of TMP (Van`t Klooster et al, 1994a).…”
Section: Discussionmentioning
confidence: 99%